The Meaning of Death in the Poem Tuan dan Pada Sebuah Maghrib by Supardi Djoko Damono: A Theological Analysis Based on Surah Ali-Imran verse 185 in Ibn Kathir's Tafsir - Izzatul Ishlah Alfatih; Muhammad Iqbal Maulana; Syarifudin Yunus (El-Ma'wa: Journal of Arabic, Translation and Linguistic, 2026)
This study uses a qualitative descriptive research method, namely providing an overview of the meaning of death in the poems "Tuan" and "Pada Sebuah Maghrib" by Sapardi Djoko Damono based on the theological analysis of Surah Ali 'Imran verse 185 in Tafsir Ibnu Katsir. The results of the study conclude that the theological analysis of the poems "Tuan" and "Pada Sebuah Maghrib" by Sapardi Djoko Damono with the approach of Surah Ali 'Imran verse 185 in Tafsir Ibnu Katsir has three main things. First, the poem "Tuan" describes death as a call from God that comes suddenly. The lyrical character who is busy ("I'm going out") asks for a delay ("Wait a minute"), which shows human unpreparedness due to being deceived by worldly pleasures. Second, the poem "Pada Sebuah Maghrib" describes the anxiety of an elderly person who feels death lurking everywhere, with the cry "Astagfirullah!" which reflects an awareness of sin and the need for God's forgiveness. Third, these two poems align with the three main points of Surah Ali 'Imran verse 185 according to Ibn Kathir's interpretation: death will surely come to every soul, worldly life is merely a deceptive pleasure, and true success is only achieved through God's grace in the afterlife. Thus, Sapardi's poems are not only literary but also serve as a medium for spiritual contemplation on the nature of life and death.